Increased MANF Expression in the Inferior Temporal Gyrus in Patients With Alzheimer Disease - Liu, Xue-Chun; Qi, Xiu-Hong; Fang, Hui; Zhou, Ke-Qing; Wang, Qing-Song; Chen, Gui-Hai (Frontiers in Aging Neuroscience, 2021)
Alzheimer’s disease (AD) is an aging-related disorder linked to dysregulation of endoplasmic reticulum stress (ERS). Its symbolic pathologic feature is the presence of extracellular senile plaques and intraneuronal neurofibrillary tangles in the brain. Mesencephalic astrocyte-derived neurotrophic factor (MANF) is a beneficial protein in endoplasmic reticulum stress that has been implicated in the pathogenesis of AD. MANF is expressed in many brain regions in different organisms. However, to date, it is unclear how MANF expression is altered in key brain regions of AD patients. Herein, in the present study, we first focused on the localization and expression levels of MANF in the inferior temporal gyrus cortex (ITGC) of postmortem brain specimens from Alzheimer’s patients (n=5), and preclinical Alzheimer's disease patients (n=5), by comparison with the age-matched non-dementia controls (n=5) by immunohistochemistry. And the double immunofluorescent staining containing MANF and NeuN (a neuron-specific nuclear protein) were performed. These findings showed that MANF was mainly expressed in neurons in the ITGC among the pre-AD, AD patients and non-dementia control samples. Strikingly, the numbers of cytoplasmic and nuclear MANF-positive neurons were significantly higher in pre-AD (Braak stages III/IV) and AD (Braak stages V/VI) patients than those in the control groups. While, the expression level of nuclear MANF was much lower than in cytoplasm in neurons. In conclusion, the current results suggested that MANF might be a potential protective factor against neural damage in the pathogenesis of AD.